Efficacy of cupping in the treatment of hypertension disease using graph colouring - Elizabeth, Marta; Yuhani, Yusof; Mohd Sham, Mohamad; Muhamad Faiz, Abu Bakar; Mohd Adhha, Ibrahim (IOP Publishing, 2019)
Cupping therapy also well known as Hijama is an ancient and holistic method for treatment variety of infirmities particularly cardiovascular diseases such as hypertension. In this method, suction mechanism used to create partial vacuum inside the cup that mobilizes the blood flow and promotes effective healing at the specific point. As practise, the selection of the points based is on patient's complaints. The aim of this study is to identify the least number yet the most effectiveness point at minimal cost to treat hypertension disease. The graph colouring method is applied, besides C# language is used to validate the result. The finding of this research indicates that the optimum number of hypertension medical cupping points is two.